The School Textbook and Identity Culture: A Content Analysis of the Civic Education Textbook - ketfi, yasmina (Journal of Social Sciences and Humanities, 2016)
The school textbook plays an effective role in helping pupils adapt to the educational environment and acquire a national culture and human values reflected in their later morals and behavior. This is what I have sought to discuss through research on the topic of the school textbook and identity culture. The study addresses this through a content analysis of the fifth-grade primary school Civic Education textbook, aiming to identify the educational values provided that respond to the pupil's needs, align with the requirements of the digital age, and consolidate the pupil's national identity.